Transformational Leadership, Organization Justice, Organization Support Perspective on Organizational Citizenship Behavior Moderating Immigration Officials - Indrias Natanael; Djamaludin Ancok; Nilam Widyarini (International Journal Labs, 2023)
This research used a quantitative approach, data collection using online questionnaires using Google Form. The respondents consisted of 196 Immigration office employees on duty in the West Java Region, including Bogor, Cirebon and Depok. Data analysis techniques using the help of SmartPLS 4.0.8.8 software. This study found a model that has not been found in previous studies, namely simultaneous leadership transformation, organizational justice, perceptions of organizational support for organizational citizenship behavior with religiosity as a coding variable. It is proved that high religious will spend time working willingly. With religiosity as a guideline in work, it is hoped that it can improve employee performance in completing work tasks for the better. This is because morality directly affects citizenship behavior, Transformational Leadership does not partially have a significant effect on citizenship behavior and religiosity cannot strengthen the relationship between transformational leadership and organizational behavior. However, organizational justice and perceived organizational support partially have a significant effect on citizenship behavior and religiosity can strengthen the relationship between organizational support perception of organizational citizenship behavior, as well as simultaneously influence on organizational citizenship behavior and religiosity strengthen the relationship between transformational leadership, organizational justice, perception of organizational support for organizational citizenship behavior.